(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This in the article small business and private entrepreneurship development directions, small business national in the economy place and importance economic indicators through illuminated. Small business and private entrepreneurship market environment fast adapt getting, employment provide income formation and that’s it through his inequality softening and medium the owners layer decision in finding advantages open given